Efficacy and Safety of Sublingual versus Vaginal Misoprostol for Pre-induction Cervical Ripening among Primigravida - Acharya, Indira; Thapa, Sumana; Chaudhary, Pushpa (Medical Journal of Shree Birendra Hospital, 2018)
Introduction: Induction of labor is an intervention intended to artificially initiate uterine contractions resulting in progressive effacement and dilatation of the cervix. This is a common intervention during pregnancy in both industrialized and non-industrialized countries.Misoprostol is the commonly used induction agent. The objective of this study was to compare the efficacy of sublingual route of misoprostol with that of vaginal for pre-induction cervical ripening at term among Primigravida. Methods: This study was a hospital based cross sectional comparative study, conducted at a tertiary center, Kathmandu over a period of 6 months extending from July 2010 to December 2010. Primigravida at 40-42 weeks of gestation who met the inclusion criteria were enrolled in this study and were randomly enrolled for sublingual misoprostol and vaginal misoprostol. Results: More women in the vaginal misoprostol group had Bishop score more than six after 8 hours of insertion of first dose (80%) compared to those who received sublingual misoprostol (48%). The mean induction to delivery interval was shorter in the vaginal misoprostol group (12.12 hours) compared to (12.96) in sublingual group. Use of oxytocin for augmentation of labour was required more in the sublingual group but the difference was not significant statistically. Conclusion: Both sublingual and vaginal routes of misoprostol administration were equally effective and appeared safe for pre-induction cervical ripening at term.